Drawing Maps for Research in Creative Writing through A/r/tography - Malilang, Chrysogonus Siddha (Resital: Jurnal Seni Pertunjukan (Journal of Performing Arts), 2018)
The essay aims to review clashes in research methodologies for creative practices–especially Creative Writing–and to propose a possible solution to bridge it. A/r/tography–a research methodology developed based on the premise of art and art creation as a rhizomatic process/activity–is elaborated here as a middle ground between opposing schemes. The author’s project of writing a collection of bilingual poems based on classical Javanese song cycle–Sekar Macapat–is presented to illustrate how a/r/tography can be used to address various multiplicities and non-linear process in creative process.